Perception Analysis of Service Quality IT Operation Study Case Of PT XYZ - Oyu Mulia Sukmana; Judijanto Judijanto; Adithya Sudiarno (Kontigensi : Jurnal Ilmiah Manajemen, 2021)
Customer satisfaction of IT service delivered by PT XYZ has become essential. Attention to develop an adequate level of customer satisfaction index in Oil and Gas Company and also to assist ICT management for continous improvement of strategy and action to meet Stakeholders needs. Using quantitative research and method Servqual questionair within five (5) variable known as Tangible, Reability, Responsiveness, Assurance and Empathy to analyze Perception an Expectation from IT Users. The result of data processing assisted with SPSS 22 to validate test and reliability of the data. Based on the research result, was obtained average value Servqual Score of Gap 5 is -0.012 on varible Assurance, which means consumers are not satisfed with the exiting service by ICT Department. In Variable of Assurance, concluded that courtesy has the highest score represent of the statement "personnel in PT XYZ consistently courteous with the users". While security has the lowest score represent of the statement "users in PT XYZ feel safe in using ICT services" in Servqual Questionair. Therefore The need for feel secure and comfort for IT Users become high consideration of ICT Department to improve its service quality in the company of PT XYZ.